Meningkatkan Hasil Belajar Siswa Melalui Pembelajaran Paikem Dengan Pendekatan Group Investigation - Ermaita Ermaita (Jurnal Studi Sosial / Journal of Social Studies, 2016)
The purpose of this research is to improve learning outcomes and the activities of a student to lose their through learning to promote disorder to PAIKEM with an approach group investigation on the subjects of of the geography of especially on any material make a map of the health of surrounding environment / school. The research is to the research done by the act of a class of. Observations the surrounding area on the the teacher in the process of implementing the of learning has been a price increase of the total value of rata-rata 48,75 on a basis of the enough on the initial conditions, become 73,35 on a basis of the good and 93,75 on a basis of the is excellent at the last a notebook detailing the development. Observations of the and activities student for the implementation of the learning increased of the initial conditions.Tujuan penelitian ini adalah untuk meningkatkan hasil belajar dan aktivitas siswa melalui pembelajaran PAIKEM dengan pendekatan Group Investigation pada mata pelajaran geografi khususnya pada materi membuat peta lingkungan sekitar / sekolah. Penelitian ini merupakan penelitian tindakan kelas. Hasil observasi terhadap kegiatan guru selama proses pelaksanaan pembelajaran mengalami peningkatan dari nilai rata-rata 48,75 dengan kriteria cukup pada kondisi awal, menjadi 73,35 dengan kriteria baik dan 93,75 dengan kriteria sangat baik pada siklus terakhir. Hasil observasi terhadap kegiatan dan kegiatan siswa selama proses pelaksanaan pembelajaran mengalami peningkatan dari kondisi awal.Kata kunci: hasil belajar, PAIKEM, group investigation